Variation in water disappearance, daily dose, and synovial fluid concentrations of tylvalosin and 3‐O‐acetyltylosin in commerical pigs during five day water medication with tylvalosin under field conditions. Issue 4 (23rd March 2018) - Canning, P.; Bates, J.; Skoland, K.; Coetzee, J.; Wulf, L.; Rajewski, S.; Wang, C.; Gauger, P.; Ramirez, A.; Karriker, L.
Abstract : Tylvalosin (TVN) is a water soluble macrolide used in swine production to treat enteric, respiratory, and arthritic pathogens. There is limited data on its distribution to synovial fluid beyond gavage studies, which do not represent field conditions. This study measured water disappearance, TVN concentration in the medicated water, daily dose, and concentrations of TVN and 3‐O‐acetyltylosin (3AT) in the synovial fluid and plasma of treated pigs over the administration period. The study emphasized understanding variation in tissue TVN concentrations within the context of a field setting. Sixty finisher pigs were housed individually with individual waterers. Six pigs were randomly allocated to the following time points for sample collection: 0, 48, 60, 72, 84, 96, 102, 108, 114, and 120 hr on medication. TVN was administered daily in the water for 5 days. Water disappearance and medicated water concentration were measured daily. At each time point, six pigs were euthanized and plasma and synovial fluid were collected for analysis. Median TVN synovial fluid concentrations ranged between <1 ng/ml (hour 0) to 3.6 ng/ml (hour 84). There was substantial variation between individual pigs for water disappearance (mean 4.36L and range 0–7.84). Median TVN water concentration was 59 ppm (range 38–75 ppm).